2022
DOI: 10.1161/circulationaha.121.056777
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarettes and Cardiopulmonary Health: Review for Clinicians

Abstract: Electronic cigarettes (e-cigarettes) are battery powered electronic nicotine delivery systems that use a propylene glycol/vegetable glycerin base to deliver vaporized nicotine and flavorings to the body. E-cigarettes became commercially available without evidence regarding their risks, long-term safety, or utility in smoking cessation. Recent clinical trials suggest that e-cigarette use with counseling may be effective in reducing cigarette use but not nicotine dependence. However, meta-analyses of observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
17

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 107 publications
(183 reference statements)
0
25
0
17
Order By: Relevance
“…This may provide a basis to understand how the heart as an organ may be more susceptible aldehyde-induced oxidative stress via NF-κB triggering a proinflammatory pathway. Ultimately, this study highlights the importance of considering the impact of genetics to develop a further understanding of the cardiovascular risks with e-cigarette aerosol use [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may provide a basis to understand how the heart as an organ may be more susceptible aldehyde-induced oxidative stress via NF-κB triggering a proinflammatory pathway. Ultimately, this study highlights the importance of considering the impact of genetics to develop a further understanding of the cardiovascular risks with e-cigarette aerosol use [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available evidence is based largely on studies of young adults who were former smokers or nonsmokers. 2b A recent study in young healthy adults who were exclusive e-cigarette users found no long- or short-term effects on endothelial function. 64 However, this study used predominantly e-cigarettes with a lower nicotine concentration than the e-cigarettes that are popular among adolescents.…”
Section: Cardiovascular Effectsmentioning
confidence: 96%
“…11 Furthermore, one must distinguish between tobacco cessation and nicotine cessation: E-cigarettes are partially successful at the former, although whether they are as good or better than other established/FDA-approved nicotine replacement therapies for nicotine cessation is debatable. 2b However, data in adolescent e-cigarette users are lacking. Indeed, although e-cigarettes in 1 study from the United Kingdom, where nicotine concentration was ≈40% lower than products in the United States, may be more effective than nicotine patches at tobacco cessation (18% versus 10%, respectively; relative risk, 1.83 [95% CI, 1.30–2.58; P <0.001]), their effectiveness in reducing nicotine consumption is absent, with 20% efficacy, whereas nicotine patches have 81% efficacy.…”
Section: Overview Of E-cigarette Types and Historymentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 studies were included [11][12][13][14][15][16][17][18][19], with a total sample size was 5161 cases. The results of the random-effects model Meta-analysis showed that the overall incidence of xerostomia was 27% [95% CI (0.17,0.37)] in the healthy smokers(Fig.…”
Section: The Incidence Of Xerostomiamentioning
confidence: 99%